ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN LAMANYA WAKTU TUNGGU RAWAT INAP (BOARDING TIME) DI UGD RS AWAL BROS PEKANBARU TAHUN 2018 - Umi Eliawati; Vetty Yulianty Permanasari (LPPM Universitas Awal Bros, 2020)
The purpose of this research is to analyse factors contributing to the boarding time in emergency department Awal Bros Pekanbaru Hospital. Variables had been analyzed are triage system, payment pattern, arrival mode, amount of diagnostic examination, amount of consulting doctors, and patients per day. This is a quantitive research, retrospective, using a cross sectional design. Waiting time conceptual model or Input/Throughput/Output model was the framework used in this study, which focusing on input and throughput process. The total sampel was 374. Data collection was using the research instrument and emergency department performance report. Data analysis was using a cross-tabulation or chi-square for bivariate analysis, and using logistic regression for multivariate analysis. The results of this bivariate analysis showed that among all varaibles, factors that contributing to boarding time was triage system ( p value= 0,001), payment pattern (p value = 0,017), amount of diagnostic examination (p value=0,001) and amount of consulting doctor (p value = 0,041). Meanwhile from the multivariate analysis showed that variables that contributing the boarding time was triage system (p value = 0,023) and amount of the diagnostic examination (p value = 0,001)